Double forehead flap reconstruction of composite nasal defects. Issue 9 (September 2016) - Zelken, Jonathan A.; Chang, Chun-Shin; Reddy, Sashank K.; Hsiao, Yen-Chang
Summary: Background and aim: Composite nasal defects require skin, framework, and lining reconstruction. The forehead flap is an ideal donor for skin coverage because of good color match and excellent donor-site healing. Intranasal flaps and grafts are reserved for lining reconstruction of small defects. Locoregional and free flaps are used for larger lining defects, but these may not be ideal or safe. The authors advocate the double forehead flap for large composite defects of the nose in a subset of patients. Methods: Three men and three women aged 55–87 years (average 74.7 years) were treated for composite nasal defects that resulted from cancer ( n = 5) and trauma ( n = 1). Skin and lining defects were >2 cm in every dimension. Double forehead flaps were raised in stages ( n = 1) or simultaneously ( n = 5), and nasal reconstruction was performed in two ( n = 1) or three stages ( n = 5). Results: Patients were followed for 19.3 months (range 13–24 months). Donor sites of flaps raised in stages healed after 3 months. When flaps were raised together, healing required 5–13 months (average 7.6 months). There were no partial or complete flap losses. None of the patients had infection, hematoma, or nerve injury. Satisfactory aesthetic results were achieved in every case. Conclusion: The authors advocate the double forehead flap for large composite nasal defects in patients who are not suitable candidates for nasolabial flaps and those who may not tolerate free tissue transfer. The advantages of this method must be weighed against the drawbacks, which include prolonged donor-site healing and elimination of the contralateral forehead flap.